Mist opportunities: haze and the composition of atmosphere. Issue 2 (4th May 2019) - Shyldkrot, Yaron
ABSTRACT: In this article, I consider what atmospheres are and how we might approach their composition in performance. Atmospheres are an emerging subject of exploration. Yet when it comes to theatre and performance, though often used to describe various experiences, what atmospheres are remains rather hazy and the ways in which they might be generated are relatively unexplored. To reflect on the hazy phenomenon of atmosphere, I turn, quite literally, to haze. I propose that haze share some similarities with atmosphere, help to materialise and arguably demonstrate our immersion in atmospheres. More specifically, I examine Jamie Lloyd's Killer (2017) and Ann Veronica Janssens' Yellowbluepink (2015) to consider the ways in which haze and visual obfuscation can be used to produce atmosphere(s). I expand on four specific strategies for the composition of atmosphere: the first impression of a space, the ecstasies of things, contrast/immediacy and duration. By bringing forward both a critical and practical approach to atmosphere, I aim to show not only how atmosphere can emerge and be understood in the theatre, or how they illuminate the felt, ephemeral and intangible capacities of scenography and performance, but also how the analysis of performance can contribute to the recent interest in atmosphere.